2020
DOI: 10.1186/s12544-020-0397-x
|View full text |Cite
|
Sign up to set email alerts
|

Materials selection for structured horizontal road markings: financial and environmental case studies

Abstract: Introduction: On majority of roads, horizontal road markings are essential safety feature that must be periodically renewed to maintain appropriate performance. Results: The use of a premium road marking system resulted in prolonged the service life as compared to a standard system, which would be financially-neutral in the long term despite much higher unit and initial costs; advantageously, 54% less glass beads and 63% less paint would be required over 10-year life cycle. When these products usage savings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…The sustainability analyses confirmed for the nth time that the lowest overall resource consumption was correlated with the longest service life. Any argumentation that the furnished values were only estimates and might correlate weakly with the outcome from the field can be dismissed upon examination of our previous work, where the data were collected in the field and the same patterns were observed [32,33,38,40,41,68]; indeed, it was those data which prompted us to undertake this effort. It should be noted that similar relative performance of standard and premium GB was also measured in the field in the United States [63].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sustainability analyses confirmed for the nth time that the lowest overall resource consumption was correlated with the longest service life. Any argumentation that the furnished values were only estimates and might correlate weakly with the outcome from the field can be dismissed upon examination of our previous work, where the data were collected in the field and the same patterns were observed [32,33,38,40,41,68]; indeed, it was those data which prompted us to undertake this effort. It should be noted that similar relative performance of standard and premium GB was also measured in the field in the United States [63].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis provided herein was not concerned with one very important practical aspect: financial analysis. Previously published calculations have demonstrated that long-term financial savings are possible with high-end RM materials despite higher unit costs [38,41]. It is worth emphasising that such financial savings would bring the most benefits if contractors were awarded long-term maintenance contracts with strict minimum performance requirements but a simultaneous choice of material selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final set of papers focuses more directly to diverse decision-making challenges that exist at various design, planning and policy levels in mobility systems. Starting from the roadway scale, Burghardt & Pashkevich focus on a challenge of selecting materials for horizontal road markings [23], while Budzynski et al focus on assessing road restraint system functionality [24]. With a lens on asset management of large number of bridges, Allah Bukhsh et al 1 propose a framework for the development of optimal multi-year maintenance plans [25].…”
mentioning
confidence: 99%